The Impact of Religious and Economic Motives on Loyalty with Satisfaction as an Intervening Variable: A Study of the Saving Customers of Bank NTB Syariah - Sanurdi Sanurdi; Muslihun Muslihun (International Journal of Islamic Khazanah, 2023)
This study aimed to investigate the influence of religious and economic motives on customer loyalty through satisfaction. It employed a descriptive research design with a quantitative approach. The population of this study comprised the saving customers of Bank NTB Syariah, and the sampling method used was quota sampling. The data collection technique involved a questionnaire adapted from relevant sources and modified to align with the study's focus. Multivariate analysis was the data analysis technique used in this research. The findings of this study revealed that the religious motive did not significantly impact customer loyalty and Satisfaction with Bank NTB Syariah. Thus, the religious motive did not create Satisfaction and Loyalty among the bank's customers. In contrast, every bank must strive for Loyalty if they want to compete in today's fiercely competitive banking industry. The economic motive significantly influenced customer loyalty and Satisfaction with Bank NTB Syariah, indicating that the financial motive created Satisfaction and Loyalty among the bank's customers. Although satisfaction statistically significantly influenced customer loyalty with Bank NTB Syariah, it could not play a significant role as an intervening variable. As shown by the t-statistics value and path coefficient, 10.559 and 0.580, respectively, the absence of a relationship between the religious motive and Loyalty implied that satisfaction could not function as an intervening variable in the relationship between the religious motive and Loyalty.